Novel Enhalus acoroides Phytosomes: Formulation, Characterization, and Bioavailability Enhancement - Siti Mardiyanti; Effionora Anwar; Yesi Desmiaty; Siti Sadiah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Enhalus acoroides (seagrass) possesses valuable bioactive compounds, including quercetin, with potential therapeutic applications, notably antidiabetic effects. However, the poor solubility and low bioavailability of compounds like quercetin limit their clinical efficacy. Phytosomes, phospholipid-based nanocarriers, represent a promising strategy to overcome these limitations. This study aimed to develop and characterize E. acoroides extract-loaded phytosomes to enhance its potential bioavailability. Methods: E. acoroides was collected, processed, and extracted using ultrasound-assisted extraction (UAE). Total phenolic (TPC) and flavonoid content (TFC) were determined. Phytosomes were prepared using the thin-layer hydration method with varying extract-to-soya lecithin ratios (F1=1:1, F2=1:2, F3=1:3). Characterization involved particle size analysis, zeta potential measurement, Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), entrapment efficiency (EE%) determination via HPLC, and in vitro dissolution studies. Results: The UAE extract yielded TPC of 0.318 ± 0.036 mg GAE/g and TFC of 1.023 ± 0.022 mg QE/g. Phytosome formulation F1 (1:1 ratio) exhibited optimal characteristics: particle size of 276.4 nm, PDI of 0.591, zeta potential of -18.0 mV, EE% of 80.47 ± 2.62%, and a spherical morphology. FTIR confirmed complexation. F1 phytosomes demonstrated significantly enhanced dissolution, releasing 87.13% of the entrapped compound over 12 hours compared to the crude extract. Conclusion: E. acoroides extract was successfully encapsulated into phytosomes using a thin-layer method. The F1 formulation (1:1 extract:phospholipid ratio) demonstrated favorable physicochemical properties (nanoparticle size, moderate stability, high EE%) and markedly improved in vitro dissolution, suggesting enhanced bioavailability potential for E. acoroides phytoconstituents.